Unusual Characteristics of the DNA Binding Domain of Epigenetic Regulatory Protein MeCP2 Determine Its Binding Specificity - Khrapunov, Sergei (American Chemical Society, 2014)
[Image: see text] The protein MeCP2 mediates epigenetic regulation by binding methyl-CpG (mCpG) sites on chromatin. MeCP2 consists of six domains of which one, the methyl binding domain (MBD), binds mCpG sites in duplex DNA. We show that solution conditions with physiological or greater salt concentrations or the presence of nonspecific competitor DNA is necessary for the MBD to discriminate mCpG from CpG with high specificity. The specificity for mCpG over CpG is >100-fold under these solution conditions. In contrast, the MBD does not discriminate hydroxymethyl-CpG from CpG. The MBD is unusual among site-specific DNA binding proteins in that (i) specificity is not conferred by the enhanced affinity for the specific site but rather by suppression of its affinity for generic DNA, (ii) its specific binding to mCpG is highly electrostatic, and (iii) it takes up as well as displaces monovalent cations upon DNA binding. The MBD displays an unusually high affinity for single-stranded DNA independent of modification or sequence. In addition, the MBD forms a discrete dimer on DNA via a noncooperative binding pathway. Because the affinity of the second monomer is 1 order of magnitude greater than that of nonspecific binding, the MBD dimer is a unique molecular complex. The significance of these results in the context of neuronal function and development and MeCP2-related developmental disorders such as Rett syndrome is discussed.